The Journey Continues: Life Transitions and Adult Learning Among the Older Women in a Continuing Care Retirement Community - Ya-Fen Lo (Adult Education Research Conference, 1999)
This study explores older women's experiences of moving and living in a continuing care retirement community. The focus is on adult learning involved in the process of adaptation. The findings suggest that transformative learning theory and continuity theory partially explain the process of successful adaptation.